Long Noncoding RNA GAS5: A New Factor Involved in Bone Diseases - Zhou, Zimo; Chen, Jiahui; Huang, Ying; Liu, Da; Chen, Senxiang; Qin, Sen (Frontiers in Cell and Developmental Biology, 2022)
Long noncoding RNAs (lncRNAs), as an important type of RNA encoded in the human transcriptome, have shown to regulate different genomic processes in human cells, altering cell type and function. These factors are associated with carcinogenesis, cancer metastasis, bone diseases, and immune system diseases, among other pathologies. Although many lncRNAs are involved in various diseases, the molecular mechanisms through which lncRNAs contribute to regulation of disease are still unclear. The lncRNA growth arrest-specific 5 (GAS5) is a key player that we initially found to be associated with regulating cell growth, differentiation, and development. Further work has shown that GAS5 is involved in the occurrence and prognosis of bone diseases, such as osteoporosis, osteosarcoma, and postosteoporotic fracture. In this review, we discuss recent progress on the roles of GAS5 in bone diseases to establish novel targets for the treatment of bone diseases.